Difference between revisions of "009B Sample Midterm 2, Problem 4"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> Evaluate the integral: ::<math>\int e^{-2x}\sin (2x)~dx</math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations:   |...")
 
(Replaced content with "<span class="exam"> Evaluate the integral: ::<math>\int e^{-2x}\sin (2x)~dx</math> <hr> '''<u>Solution</u>''' 009B Samp...")
 
(4 intermediate revisions by the same user not shown)
Line 3: Line 3:
 
::<math>\int e^{-2x}\sin (2x)~dx</math>
 
::<math>\int e^{-2x}\sin (2x)~dx</math>
  
 +
<hr>
 +
[[009B Sample Midterm 2, Problem 4 Solution|'''<u>Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;
 
|-
 
|Review integration by parts
 
|}
 
  
'''Solution:'''
+
[[009B Sample Midterm 2, Problem 4 Detailed Solution|'''<u>Detailed Solution</u>''']]
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|We proceed using integration by parts. Let <math style="vertical-align: -5px">u=\sin(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx</math>. Then, <math style="vertical-align: -5px">du=2\cos(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}</math>.
 
|-
 
|So, we get
 
|-
 
| &nbsp;&nbsp; <math style="vertical-align: -14px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}-\int \frac{e^{-2x}2\cos(2x)~dx}{-2}=\frac{\sin(2x)e^{-2x}}{-2}+\int e^{-2x}\cos(2x)~dx</math>.
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we need to use integration by parts again. Let <math style="vertical-align: -5px">u=\cos(2x)</math> and <math style="vertical-align: 0px">dv=e^{-2x}dx</math>. Then, <math style="vertical-align: -5px">du=-2\sin(2x)dx</math> and <math style="vertical-align: -13px">v=\frac{e^{-2x}}{-2}</math>.
 
|-
 
|So, we get
 
|-
 
| &nbsp;&nbsp; <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}-\int e^{-2x}\sin(2x)~dx</math>.
 
|-
 
|
 
|}
 
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
|-
 
|Notice that the integral on the right of the last equation in Step 2 is the same integral that we had at the beginning of the problem.
 
|-
 
|So, if we add the integral on the right to the other side of the equation, we get
 
|-
 
| &nbsp;&nbsp; <math>2\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-2}+\frac{\cos(2x)e^{-2x}}{-2}</math>&thinsp;.
 
|-
 
|Now, we divide both sides by 2 to get
 
|-
 
| &nbsp;&nbsp; <math>\int e^{-2x}\sin (2x)~dx=\frac{\sin(2x)e^{-2x}}{-4}+\frac{\cos(2x)e^{-2x}}{-4}</math>&thinsp;.
 
|-
 
|Thus, the final answer is <math style="vertical-align: -13px">\int e^{-2x}\sin (2x)~dx=\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math>.
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
| &nbsp;&nbsp; <math>\frac{e^{-2x}}{-4}((\sin(2x)+\cos(2x))+C</math>
 
|}
 
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:10, 12 November 2017

Evaluate the integral:


Solution


Detailed Solution


Return to Sample Exam